1978
DOI: 10.1039/dt9780000503
|View full text |Cite
|
Sign up to set email alerts
|

Protonation of the decavanadate(6–) ion: a vanadium-51 nuclear magnetic resonance study

Abstract: The first protonation site of [Vlo02,]6differs both from the second protonation site and from the site of preferential interaction with aqueous manganese(i1) ion. It is probably an out-of-plane apex, and not a bridging oxygen as has recently been proposed. The 61V n.m.r. linewidths are almost independent of direct protonation but depend in-Coventry CV4 7AL directly on more distant protonation. THE isopolyvanadate ion [Vl,02,]6-has the structure shown in Figure 1 in all the crystals in which it has so far Q f F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 0 publications
2
67
0
Order By: Relevance
“…Since most of the vanadate species can be detected by 51 V NMR spectroscopy, it was observed that the spectra of decavanadate stock solution, 50 mM in total vanadium, at pH 7.0, contained mainly decameric species once the three signals from decameric vanadate species, ascribed to the three vanadium atoms of the decavanadate structure [28], are observed: V10A at À517 ppm, V10B at À501 ppm, V10C at À426 ppm and a weak signal (V1) at À562 ppm (Fig. 1A).…”
Section: Characterization Of Vanadate Solutionsmentioning
confidence: 99%
“…Since most of the vanadate species can be detected by 51 V NMR spectroscopy, it was observed that the spectra of decavanadate stock solution, 50 mM in total vanadium, at pH 7.0, contained mainly decameric species once the three signals from decameric vanadate species, ascribed to the three vanadium atoms of the decavanadate structure [28], are observed: V10A at À517 ppm, V10B at À501 ppm, V10C at À426 ppm and a weak signal (V1) at À562 ppm (Fig. 1A).…”
Section: Characterization Of Vanadate Solutionsmentioning
confidence: 99%
“…Klemperer & Shum (1977) and Howarth & Jarrold (1978) have determined the protonation sites of (H2VI0028) 4-in solution using 170 NMR and 5W NMR spectroscopy, respectively. The former authors found that Ob and Od type (see Table 2) are the most basic oxygens, Ob being more basic than Od, while the latter authors pointed out that the most probable protonation sites are at the apical oxygens Of and Og.…”
Section: Diagonal Terms Terms Are V-o Distances Upper Diagonal Termsmentioning
confidence: 99%
“…6.6. Furthermore, another m 2 -O site (E) is extraordinarily slow to exchange (Figure 1 c) [2,3] with pK x values of: pK 1 = 6.0; pK 2 = 3.74, and pK 3 = 1.6 (I = 0.6 m). Using these equilibrium constants, the [Nb 10 O 28 ] 6À species dominates at most pH conditions of this study, with the monoprotonated form [HNb 10 O 28 ]…”
mentioning
confidence: 99%